Establishing a customer satisfaction survey as a way to measure the effectiveness and efficiency of the value-added services offered to the customers of First Gen Corporation - Galang, Fatima M. (Animo Repository, 2022)
You can't look at the competition and say you'll do it better. You must look at the competition and say you will do differently." A quote by Steve Jobs can best describe how a company formulates its competitive advantage that serves as one of its pillars in sustaining a business not just in the present but more so in the future. One of First Gen Corporation's competitive advantages is the Value Added Services provided to the existing customers on top of the expected service of energy generation. These Value Added Services have different types that range from Capability Building, Technical Services, Corporate Social Responsibility, Customer Events, and Sponsorships, depending on what the customer requests and the amount of the Value Added Service/s that is requested. The paper will discuss the Value Added Services in detail and my Integrated Action Research teammate's journey in crafting ways to measure the Effectiveness and Efficiency of the Value Added Services we offer to our customers. The paper will also walk the reader on the different methods used to collaborate and dig deeper into the concept of Customer Satisfaction metrics and surveys and why the team has decided to use them as our primary measure of effectiveness and efficiency. Moreover, the paper also focused on the implementation or how the team encouraged responses to the survey. It will again dig deeper into the challenges of having a high response rate and the importance of why a high response rate should be achieved. Lastly, the paper also details the methodologies used in constructing the problem and frameworks used to determine how to measure the effectiveness and efficiency of the company's value-added services. Together with the use of different meta-learning reflections, these could be adjusted or tweaked into the paper's various cycles.